Unilateral genu recurvatum: A case report - Vladan; Aleksic, Bojana; Velickovic, Veljko; Cucakovic, Filip (Medical Research, 2026)
Introduction: Genu recurvatum is characterized by knee hyperextension, gait instability, and pain. It is rarely encountered in routine orthopedic practice, and evidence regarding optimal treatment strategies remains limited. In this case, the absence of trauma, associated varus malalignment, and the unilateral presentation further increased the complexity, with progressive worsening observed over a three-year follow-up period. This report presents a rare case of unilateral genu recurvatum of unknown etiology, treated with corrective proximal tibial osteotomy and posterior tibial slope adjustment, along with postoperative outcomes and a brief review of the literature. Case Presentation: A 32-year-old male patient presented with unilateral genu recurvatum and an intact posterior cruciate ligament (PCL), confirmed by MRI and arthroscopy. Preoperative planning was based on MSCT analysis. An open-wedge proximal tibial corrective osteotomy with plate fixation was performed. Under C-arm–guided fluoroscopy, the planned correction and posterior tibial slope were achieved. The posterior tibial tilt increased from 94° to 101°, improving knee stability and correcting the deformity. Conclusion: Corrective proximal tibial osteotomy with posterior slope adjustment represents an effective treatment option for unilateral genu recurvatum of unknown etiology. This technique provides reliable mechanical axis correction, joint stabilization, and favorable clinical outcomes with relatively rapid postoperative recovery.